Assessment of self-perceived oral malodor, oral hygiene practices, and smoking habits among dental and engineering students: A cross-sectional study - Rahul Nivrutti Deokar; Arun Suresh Dodamani; K Prashanth Vishwakarma; Abhijit Ashok Hoshing; Vardhaman Mulchand Jain; Gaurao Vasant Mali (Wolters Kluwer Medknow Publications, 2022)
Aim and Objectives: This study aimed to assess the prevalence and knowledge of self-perceived oral malodor, oral hygiene practices, and smoking habits among dental and engineering students of Dhule district. Materials and Methodology: A structured self-administered, close-ended questionnaire was prepared and was given to 435 dental and engineering e students. This was to assess the self-reported perception of oral breath, awareness of bad breath, timing of bad breath, treatment received for bad breath, oral hygiene practices, caries and bleeding gums, dryness of the mouth, smoking and tea-drinking habits, and tongue coating. The students who responded to the questionnaire were included in the study. Informed consent was obtained from the subjects willing to participate in the study. Results: Toothbrushing was prevalent among 100% of dental students and 87% of engineering students. Self-perception of oral malodor was prevalent among 7% of dental students and 66% of engineering students. Smoking habit was prevalent in 26% of engineering students and 8% of dental students, for which self-treatment was sought for bad breath by 6% of dental students and 8% of engineering students. Conclusion: Dental students had increased awareness regarding self-perceived oral malodor, oral hygiene practices, and smoking habits compared to engineering students.